2015
DOI: 10.1210/en.2015-1725
|View full text |Cite
|
Sign up to set email alerts
|

α-Cell Dysfunctions and Molecular Alterations in Male Insulinopenic Diabetic Mice Are Not Completely Corrected by Insulin

Abstract: Glucagon and α-cell dysfunction are critical in the development of hyperglycemia during diabetes both in humans and rodents. We hypothesized that α-cell dysfunction leading to dysregulated glucagon secretion in diabetes is due to both a lack of insulin and intrinsic defects. To characterize α-cell dysfunction in diabetes, we used glucagon-Venus transgenic male mice and induced insulinopenic hyperglycemia by streptozotocin administration leading to alterations of glucagon secretion. We investigated the in vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…Moreover, cultured islet cells responded properly to the physiologically relevant secretagogues (high glucose for insulin, and arginine for glucagon), by inducing the respective hormone secretion about twofolds (Figure 4F). In line with these data, our recent work demonstrated that primary α-cells isolated from ProGcg-Venus mice responded to high glucose by a reduction in glucagon release (33), thus giving the opportunity to perform hormone secretion studies by these cells in vitro . This is particularly important for α-cells, since in mixed islet cell populations the glucagon secretion is altered by the amount of insulin secreted by adjacent β-cells, which represent the cell majority (34, 35).…”
Section: Discussionmentioning
confidence: 52%
“…Moreover, cultured islet cells responded properly to the physiologically relevant secretagogues (high glucose for insulin, and arginine for glucagon), by inducing the respective hormone secretion about twofolds (Figure 4F). In line with these data, our recent work demonstrated that primary α-cells isolated from ProGcg-Venus mice responded to high glucose by a reduction in glucagon release (33), thus giving the opportunity to perform hormone secretion studies by these cells in vitro . This is particularly important for α-cells, since in mixed islet cell populations the glucagon secretion is altered by the amount of insulin secreted by adjacent β-cells, which represent the cell majority (34, 35).…”
Section: Discussionmentioning
confidence: 52%
“…Moreover, such system allows to dissect the temporal profiles of islet hormone secretion, along with the molecular characterization of the islet cellular oscillator . Of note, the recent development of highly specific fluorescent islet cell reporters has opened new horizons for studying separate α‐ and β‐cell functions in mice, and in humans …”
Section: Discussionmentioning
confidence: 76%
“…69 Moreover, such system allows to dissect the temporal profiles of islet hormone secretion, along with the molecular characterization of the islet cellular oscillator. 116 Of note, the recent development of highly specific fluorescent islet cell reporters has opened new horizons for studying separate αand β-cell functions in mice, 90,91,124 and in humans. 75,125 Additional challenge in translating clock studies from mouse/rat to human models is related to the peripheral clock differences of nocturnal vs. diurnal species.…”
Section: Cell-autonomous Circadian Oscillations In the Endocrine Pancmentioning
confidence: 99%
“…Murine primary cell preparation and cellular cultures. At the end of the protocol, primary α-Venus + and L cells and primary β-Cherry + cells from sham, ovx, ovx+v, and ovx+E 2 mice were separated from non-Venus and non-Cherry cells by FACS using Bio-Rad S3 and Moflo Astrios, after standard isolation procedures on the pancreas and small intestine, as described (50)(51)(52). FACS-purified α-, β-, and L cells were collected in acid/ethanol mixture (1.5% HCl/75% ethanol) for glucagon, insulin, and GLP-1 cellular content measurements or in RNAse-free lysis buffer (Qiagen RLT+ Buffer) for gene expression analyses.…”
Section: Methodsmentioning
confidence: 99%